Using Extinction to Reduce Student Phubbing Behavior - Awalya Siska Pratiwi; Arbin Janu Setiyowati (Jurnal Penelitian Bimbingan dan Konseling, 2024)
The purpose of this article is to show that phubbing behavior can be reduced by using extinction techniques. The method in this article uses a qualitative study in the form of a literature review. The literature review method is used to describe the application of extinction to reduce phubbing behavior. Extinction is the elimination or deletion of certain responses to reduce unwanted behavior, the behavior in question is phubbing behavior. So that phubbing behavior can be reduced using the Extinction method, appropriate procedures are needed, namely by seeking reinforcement, communicating the target behavior clearly and firmly, carrying out extinguishing procedures over a long period of time, and finally combining it with other procedures.